USP4 promotes proliferation and metastasis in human lung adenocarcinoma - Yamin Wei; Shanwang Wei; Zhongteng Lei; Yan Zhang; Jinxiao Wu; Jinli Huang; Lijuan Fu; Zhimeng Li; Guiying Huang; Yuanna Liang; Jinhua Zheng (Scientific Reports)
Abstract Research the expression of USP4 in lung adenocarcinoma and its correlation with clinicopathological features and prognosis analysis, to explore the invasion and metastasis mechanism of USP4 in lung adenocarcinoma, and to clarify the mechanism of USP4’s involvement in the occurrence and development of lung adenocarcinoma. The expressions of USP4, VEGF, MMP2 and Ki67 in lung adenocarcinoma and adjacent tissues of 139 patients with lung adenocarcinoma were detected by immunohistochemical method, and the correlation between expression and clinicopathological features and survival curve were analyzed by statistical method. The expression of USP4 was interfered by LIP-2000 cell transfection technology, and the expression of USP4 and its related factors in protein level was detected by Western Blot, and their correlation was analyzed. After silencing USP4 expression, the effects of USP4 on proliferation, invasion and migration of lung adenocarcinoma cells were detected by cell scratches assay, MTT assay, Transwell assay and tumorigenesis assay in nude mice. The expression of USP4 in lung adenocarcinoma tissues was higher than that in normal adjacent tissues, and the high expression of USP4 was significantly correlated with the differentiation degree of lung adenocarcinoma, clinical stage and pathological grade lymph node metastasis. After silencing USP4 expression, the expression of cyclin apoptosis protein invasion related proteins and phosphorylation factors were affected, and then cell migration and the proliferation ability decreased, the number of invasion and metastasis decreased, and the tumor volume decreased in nude mice. USP4 may play a certain role in the invasion and metastasis of lung adenocarcinoma by regulating the expression of tumor-related factors and affecting the prognosis of patients with lung adenocarcinoma. USP4 can be used as a potential therapeutic target for clinical diagnosis of lung adenocarcinoma and provide a new opportunity for clinical research on lung adenocarcinoma.